Archbishops House, Port of Spain, Trinidad - Rice, Ben (The Bonanza, Smith Bros and Co., Trinidad, 2010)
Constructed in 1904, this historic building is one of the 'Magnificent Seven' located around the Queen's Park Savannah, Port of Spain, Trinidad. It serves as the residence of the Roman Catholic Archbishop of the Diocese.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Archbishop's House, The; Catholic institutions--Buildings; Architecture--Trinidad and Tobago; Bishops--Dwellings--Trinidad and Tobago; Local term--Magnificent Seven (The) - Port of Spain; Historic buildings--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain